“Racism is still alive, despite science, education and rationality”: An interview with Munanga - Moraes, Fabio Monteiro de (Latitude, 2024)
In mid-2023, at the suggestion of my master's supervisor, PhD Teacher Cristiano das Neves Bodart, I was looking for a personality from the academic-scientific world, whose productions and trajectory dialogued in some way with my research on the teaching of ethnic-racial relations in sociology classes in High School. In August, after attending PhD Teacher Kabengele Munanga's lecture on education at the 10th Maceió Book Biennial (10ª Bienal do Livro de Maceió), I left there impacted by his exhibition and decided to try to interview him. From then on, we made contact with Teacher Munanga, who responded to us in a very generous way, granting us the present interview. We then elaborated seven questions that promoted reflections on the notion of place of speech, structural racism, identitarianism and class struggle, the anti-racist struggle in Brazil and issues around Law No. 10.639/03.